HUBUNGAN ANTARA LEMAK VISERAL DAN FUNGSI KOGNITIF PADA MAHASISWA FAKULTAS KEDOKTERAN UPN "VETERAN" JAKARTA - Anisa Novita Budiman (2023)
During COVID-19, there was a change in student lifestyle, which triggered visceral fat accumulation. The accumulation of visceral fat is one of the causes of systemic inflammation, which is dangerous for the integrity of the brain and can potentially reduce cognitive function. This study aimed to determine the relationship between visceral fat and cognitive function among medical students. This study used a cross-sectional design on 73 Faculty of Medicine UPN "Veteran" Jakarta students who met the criteria and were selected using a simple random sampling technique. Measurement of visceral fat used the Tanita Body Composition Analyzer (MC 980 Plus), while measures of cognitive function used a questionnaire Digit Symbol Substitution Test. Data were analyzed using the Spearman, Chi-square, and Mann-Whitney tests. The results showed that there were differences in sex and BMI characteristics between normal and high visceral fat groups (p < 0.05). There were no characteristic differences in age, consumption of junk food, and physical activity between the visceral fat groups (p > 0.05). Spearman test results showed a relationship between visceral fat and cognitive function (p = 0.000; r = -0.561). The higher the visceral fat, the lower the cognitive function.